Conocimiento sobre planificación familiar en las adolescentes embarazadas que acuden al servicio de hospitalización del Hospital Isidro Ayora de la ciudad de Loja - Salazar Tello, Iván Oswaldo (2016)
This study was based mainly on valuing the knowledge it has more than enough family planning, of the gestating adolescents, toasting of this way a better information to the patient and to diminish the number of not planned pregnancies. It is a work of descriptive and traverse carried out type, in the Regional Hospital Isidro Ayora of the City of Loja. 90 gestating patients were studied, to investigate the knowledge it has more than enough family planning, applying a survey to value this knowledge. It was determined that the studied population's 75% has knowledge of birth-control methods, the used method it was the natural one, followed by that of barrier; the age that prevails in the gestating adolescents oscillates among 16 to 19 years and our population's 80% it studied with the first pregnancy. Key words: Adolescents, Pregnancy, family Planning.